PENGARUH E-LEARNING TERHADAP HASIL BELAJAR SISWA PADA KONSEP SISTEM REPRODUKSI MANUSIA - abdul wadud (INFOKES (Informasi Kesehatan), 2022)
Research has been carried out with the title "The Influence of E-learning on student learningoutcomes on the concept of the human reproductive system". This study aims to determine theeffect of e-learning on student learning outcomes on the concept of the human reproductive system.The research method used is quasi-experimental and the design used is pretest-posttest controlgroup design. The study was conducted on students of class XI IPA 4 as a control class and XI IPA5 as an experimental class at MA Negeri 1 Bandung with 31 students in each class. Sampling wasdone with a purposive sampling technique. To obtain the required data, the instruments used aremultiple choice questions as primary data and questionnaires as secondary data. Based on dataprocessing, the average posttest learning outcomes for the experimental class was 63.23 and thecontrol class was 61.74 with the results of hypothesis testing Z count = 0.53 in the Z tableacceptance area of 1.96. Based on these results, there is no significant effect of learning throughe-learning on student learning outcomes on the concept of the human reproductive system. It canbe concluded that e-learning has the same effect as multimedia learning on student learningoutcomes.Keywords: E-Learning, Learning Outcomes, Human Reproductive System